Determination Of Mitragynine As A Substrate, Inducer, Or Inhibitor Of P-Glycoprotein Drug Transporter, And Prediction Of Drug-Herb Interaction Risks - Rusli, Noradliyanti (2017)
P-glycoprotein (P-gp) is a multidrug transporter, mainly expressed in the intestinal tissue as a secretory efflux protein. Changes in the activity, gene and protein expression of P-gp caused by drugs or herbal compounds will affect oral drug bioavailability and may potentially lead to drug-drug or drug-herb interactions. Mitragyna speciosa Korth or Ketum is traditionally used for various ailments but due to its euphoric effects, this plant is often misused by the local population. Although Ketum is a controlled substance in most Asian countries, including Malaysia, its use is not strictly regulated in other parts of the world. Mitragynine is a major bioactive component in the crude extract of the plant and the safety of this alkaloid causing adverse drug interaction via P-gp has not been fully investigated.